BASIC CONCEPTS OF EDUCATIONAL MANAGEMENT - Dantika, Fina Azizah; Kamaludin, Kamaludin; Anwar, Miftahul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Management is the science and art of managing the process of utilizing human resources and other sources effectively and efficiently to achieve a certain goal. The concept of educational management, roles and functions and the scope of educational management are discussed in this research. The method used in this research is descriptive by explaining literature studies regarding the basic concepts of educational management. Some of the literature presented is used as a reference for this research. The aim of this research is to know and understand the concept of educational management, the role, function and scope of educational management itself. The results of the research show that management is a science and art that regulates the process of utilizing human resources and other resources effectively and efficiently to achieve a certain goal. The scope and functions of management are related to each other starting from planning, organizing, implementing and monitoring. Education management is also the role of managing an educational institution by using all resources efficiently to achieve educational goals effectively.